ANALISIS DAN PERANCANGAN ECOMMERCE PADA BATIK TULIS TENGAH SAWAH NGADIROJO - Tri Hariyati; Bambang Eka Purnama; Sukadi Sukadi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2018)
Abstract Electronic Commerce is defined as the process of buying and selling of products, services and information that will be conducted electronically by using computer network. E-Commerce can involve electronic funds transfer, electronic data interchange, automated inventory management systems, and automated data collection systems. Batik tulis Tengah Sawah Ngadirojo to date in the marketing and sales process is still conventional. The purpose of this study was to analyze the sales system is running and doing the design of e-commerce in the Batik Tulis Tengah Sawah located in Ngadirjo. The method used is to provide an overview of e-commerce to the Batik Tulis Tengah Sawah Ngadirojo. Based on these issues, then made the design of e-commerce in the Batik Tulis Tengah Sawah Ngadirojo and is expected to help consumers to find out the availability of existing products without having to visit a workshop. With the design of ecommerce is that consumers can make purchases online and payment products made through bank transfer. Addition was made to expand the marketing and sales of products, e-commerce is expected to improve the quality of service to consumers.